Porphyrin-Based Nanomedicines for Cancer Treatment - Xue, Xiangdong; Lindstrom, Aaron; Li, Yuanpei (Bioconjugate chemistry, 2019)
As unique molecules with both therapeutic and diagnostic properties, porphyrin derivatives have been extensively employed for cancer treatment. Porphyrins not only show powerful phototherapeutic effects (photodynamic and photothermal therapies), but also exhibit excellent imaging capacities, such as near-infrared fluorescent imaging (NIRFI), magnetic resonance imaging (MRI), photoacoustic imaging (PAI), positron emission tomography (PET), and single-photon emission computed tomography (SPECT). In order to take advantage of their robust phototherapeutic effects and excellent imaging capacities, porphyrins can be used to create nanomedicines with effective therapeutic and precise diagnostic properties for cancer treatment. In this Review, we summarize porphyrin-based nanomedicines which have been developed recently, including porphyrin-based liposomes, micelles, polymeric nanoparticles, peptide nanoparticles, and small-molecule nanoassemblies, and their applications on cancer therapy and diagnosis. The outlook and limitation of porphyrin-based nanomedicines are also reviewed.